Effectiveness of Mobile App-Based Interventions to Support Diabetes Self-Management: A Systematic Review - Dia Amalindah; Agnestria Winarto; Anggun Hidayatur Rahmi (Universitas Airlangga, 2020)
Introduction: Diabetes is a major health problem worldwide due to its rapidly growing prevalence and high disease burden. Nowadays, the evolution of mobile technology provides a large number of health-related mobile applications (apps) mainly focusing on the self-management of diabetes. The aim of this paper is to systematically review the effectiveness of mobile app-based self-management interventions on clinical and/or psychological outcomes in patients with type 1 and type 2 diabetes.Methods: A systematic search of four databases (Scopus, Medline, CINAHL, and Proquest) was conducted using the terms